Kinerja Pembiayaan UMKM Terhadap Profitabilitas Bank Umum Syariah di Indonesia - Marwah Nur Al-Zauqi; Iwan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study aims to determine how MSME financing and Capital Adequacy affect the profits of Islamic commercial banks. This study uses a quantitative approach that analyze secondary data from statistic of Islamic Bank in Indonesia period 2016-2019. The analysis used multiple linear regression analysis methods. Data processing uses eviews program. The results of this study indicate that MSME financing has a significant positive effect on Return on Asset. Capital Adequacy Ratio has a significant positive effect on Return on Asset. MSME financing and Capital Adequacy Ratio has a simultant effect to Return on Asset. The results of this study are expected to be a material consideration for Islamic commercial banks in providing MSME financing and maintaining capital adequacy.